SIMULASI PERANCANGAN WIRELESS LAN PADA AREA PERKANTORAN - Kusuharto, Indra; Wiyanto, Eddy (Teknik dan Ilmu Komputer, 2012)
Basically, LAN and wireless LAN Â are both computer networks that are connected to each other, which distinguishes between the two is the media data used. LAN still using cable as a medium for data traffic, while the wireless LAN using a medium wave radio/air. Wireless LAN networks are designed in this paper is intended for an office area which consists of six floors where on each floor there is an access point which is configured with a static route to deliver data packets to their proper destinations via routes that were generated manually. In designing this network simulation authors choose references software from Cisco that is Packet Tracer 5.3. From the simulation results obtained the conclusion that the configuration of the Wireless LAN was able to work well.Â Keywords: wireless LAN, static route, host, packet tracer